2017
DOI: 10.1016/j.redox.2016.12.005
|View full text |Cite|
|
Sign up to set email alerts
|

ROS via BTK-p300-STAT1-PPARγ signaling activation mediates cholesterol crystals-induced CD36 expression and foam cell formation

Abstract: In understanding the mechanisms of cholesterol in the pathogenesis of atherosclerosis, previous studies from other laboratories have demonstrated that cholesterol crystals (CC) induce scavenger receptor CD36 expression and NLRP3-mediated inflammasome formation. In elucidating the mechanisms by which CC could enhance CD36 expression and foam cell formation, here we report that CC via NADPH and xanthine oxidases-mediated ROS production activates BTK, a non-receptor tyrosine kinase. In addition, CC induce p300 ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 54 publications
2
44
0
Order By: Relevance
“…It should be pointed out that we have reported previously that 15(S)-HETE induces ROS production in monocytes via an interdependent activation of both NADPH oxidase and xanthine oxidase (23). In line with this observation, recently we have also demonstrated a similar interdependency between NADPH oxidase and xanthine oxidase activation in the production of ROS by cholesterol crystals in mediating CD36 expression and foam cell formation (50). Many growth factors and cytokines produce ROS in modulating cell proliferation, migration, or apoptosis mostly via activation of NADPH oxidase (51,52).…”
Section: Tf Role In 15(s)-hete-induced Monocyte Migrationsupporting
confidence: 85%
“…It should be pointed out that we have reported previously that 15(S)-HETE induces ROS production in monocytes via an interdependent activation of both NADPH oxidase and xanthine oxidase (23). In line with this observation, recently we have also demonstrated a similar interdependency between NADPH oxidase and xanthine oxidase activation in the production of ROS by cholesterol crystals in mediating CD36 expression and foam cell formation (50). Many growth factors and cytokines produce ROS in modulating cell proliferation, migration, or apoptosis mostly via activation of NADPH oxidase (51,52).…”
Section: Tf Role In 15(s)-hete-induced Monocyte Migrationsupporting
confidence: 85%
“…Under conditions of oxidative stress, Nrf2 is translocated to the nucleus where it initiates transcription of antioxidative genes including CD36 45 . CD36 expression has also been shown to be stimulated by metabolites of arachidonic acid through ROS production 46 , and a recent study showed that ROS mediates cholesterol crystals-induced CD36 expression and foam cell formation 47 . Thus, the increased production of ROS in Vim −/− macrophages could potentially mediate increased expression of CD36 through several mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CD36 in macrophages is upregulated by several proatherogenic stimuli, such as oxLDL (Endemann et al, 1993), palmitate (Kim et al, 2017), and dysfunctional HDL from coronary artery disease (CAD) patients (Sini et al, 2017). The CD36 gene transcription is regulated by peroxisome proliferator-activated receptor-g (PPARg) (Nagy et al, 1998;Tontonoz et al, 1998), nuclear erythroid-related factor 2 (Nrf2) (Ishii et al, 2004;Olagnier et al, 2011), as well as by signal transducer and activator of transcription 1 (STAT1) (Kotla et al, 2017) pathways. In addition, CD36 expression can also be regulated by retinol-binding protein 4 (Liu et al, 2017b), protein kinase Cu (PKCu)/activating transcription factor 2 (Raghavan et al, 2018), epidermal growth factor receptor (Zeboudj et al, 2018), trimethylamine N-oxide (Geng et al, 2018), NACHT, LRR, and PYD domains-containing protein 3 inflammasome (Chen et al, 2018b), transient receptor potential vanilloid 4 (TRPV4) (Goswami et al, 2017), cellular communication network factor 3 (Shi et al, 2017), melanocortin 1 receptor (Rinne et al, 2017), cluster of differentiation 146 (CD146) (Luo et al, 2017), triggering receptor expressed on myeloid cells (Joffre et al, 2016), cyclophilin A (Ramachandran et al, 2016), and many others.…”
Section: A Cholesterol Uptakementioning
confidence: 99%